3D‐Printed Structured Reactor with Integrated Single‐Atom Catalyst Film for Hydrogenation. Issue 14 (29th April 2022) - Vilé, Gianvito; Ng, Derrick; Xie, Zongli; Martinez‐Botella, Ivan; Tsanaktsidis, John; Hornung, Christian H.
Abstract: Structured catalytic reactors are gaining considerable attention for integrated chemical synthesis because they offer enhanced mass transfer and easy catalyst recovery. In this paper, a new, cost‐effective design strategy that combines 3D printing and single‐atom catalysis is presented, enabling the construction of an integrated mixer‐based reactor insert, coated with a thin single‐atom catalytic layer. The material has been characterized from the nano to the macro scale to unlock structure‐property relationships. The performance of the catalyst structure was evaluated via hydrogenation of two model compounds used in the flavorings and fragrances industry. The structured catalytic reactor was active, selective, and reusable several times without apparent drop in performance. This immobilized catalyst system removes the need for catalyst separation post‐reaction, and enables modern synthesis options catalyzed over atomically‐precise nanomaterials. Abstract : A structured 3D‐printed microreactor coated with a single‐atom catalytic layer is presented and evaluated for continuous‐flow hydrogenations. The work paves the way for the practical and industrial‐scale utilization of single‐atom catalysts in structured form.